DOA DALAM GENGGAMAN: FENOMENA APLIKASI PENGINGAT IBADAH DI KALANGAN GEN Z - Fata Fata (NIHAYAH: Journal of Islamic Studies, 2025)
This study explores the phenomenon of prayer reminder applications among Generation Z within the context of digital religiosity transformation. The rapid advancement of digital technology, particularly smartphones, has introduced new forms of spiritual engagement, including "micro-spirituality" and notification-based religious practices. Using a mixed-methods approach, this research combines a survey of 500 application users aged 15–25 and in-depth interviews with 20 intensive users. Content analysis was also conducted on ten of the most popular prayer reminder apps in Indonesia, along with observations of related online discussion forums. The findings reveal a high frequency of app usage, especially features like prayer reminders, daily dhikr, and fasting schedules. While these apps enhance religious discipline, they also give rise to the phenomenon of “checklist spirituality,” which may diminish the reflective essence of worship. Moreover, dependence on digital notifications can lead to spiritual distractions and psychological challenges such as fear of missing out (FOMO). This study underscores the necessity of designing more adaptive, contextual, and ethically grounded religious applications to meet the challenges of mediated religion. The implications highlight the need to integrate spiritual authenticity with technological sophistication in shaping a new form of religiosity that retains essential values in contemporary Islamic practice.